2004
DOI: 10.1002/biof.5520200304
|View full text |Cite
|
Sign up to set email alerts
|

In vitro protective effect of Rhodiola rosea extract against hypochlorous acid‐induced oxidative damage in human erythrocytes

Abstract: Rhodiola rosea L. (Crassulaceae) is a plant living at high altitudes in Europe and Asia. Its roots have long been used in the traditional medical system of these geographical areas to increase the organism resistance to physical stress; today, it has become an important component of many dietary supplements. In this study we investigate the antioxidant capacity of the R. rosea aqueous extract evaluating its ability to counteract some of the main damages induced by hypochlorous acid (HOCl), a powerful oxidant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 36 publications
(86 reference statements)
2
37
0
Order By: Relevance
“…H. perforatum extract takes an intermediate place, and G. lutea extract possesses the lowest antioxidant capacity. Our results are in agreement with other studies that have demonstrated a high antioxidant potential for extracts of R. rosea [23][24][25][26], R. canina [9,[27][28][29] and H. perforatum [11,30,31]. Extracts from G. lutea rhizomes were shown to have no such powerful antiradical activity in vitro as plants rich in polyphenols [18,32] which is consistent with our results.…”
Section: Abts•+ Scavenging Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…H. perforatum extract takes an intermediate place, and G. lutea extract possesses the lowest antioxidant capacity. Our results are in agreement with other studies that have demonstrated a high antioxidant potential for extracts of R. rosea [23][24][25][26], R. canina [9,[27][28][29] and H. perforatum [11,30,31]. Extracts from G. lutea rhizomes were shown to have no such powerful antiradical activity in vitro as plants rich in polyphenols [18,32] which is consistent with our results.…”
Section: Abts•+ Scavenging Activitysupporting
confidence: 93%
“…In this study, we used S. cerevisiae to assess antioxidant and prooxidant properties of four medicinal plants growing in Ukrainian Carpathian Mountains, Rhodiola rosea L., Gentiana lutea L., Rosa canina L., and Hyperycum perforatum L., which are also distributed in other temperate areas of Europe. A number of studies have reported on antioxidant activities of R. rosea [23][24][25][26], R. canina [9,[27][28][29], H. perforatum [11,30,31], and G. lutea [18,32,33]. However, little attention has paid to prooxidant properties of these plants, and the findings are focused mainly on reduction of antioxidant activity of plant extracts with increasing their doses [9].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Although the mechanism in which plant adaptogens increase stress resistance is still a matter of debate, cell studies have shown an involvement of pathways leading to synthesis of one or more of the heat shock proteins as well as a development of oxidative stress resistance (Afanasiev et al 1996;Chiu et al 2003;De Sanctis et al 2004;Wiegant et al 2008). The IGF-1 signal transduction pathway has been demonstrated to play a crucial role in the regulation of both stress resistance and longevity in different model systems (Partridge and Gems 2002;Cypser et al 2006;Houthoofd and Van Fleteren 2007;McElwee et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…11,12) Salidroside (SA), a natural compound from Rhodiola rosea L., is a major active ingredient responsible for most pharmacological effects of Rhodiola, such as anti-oxidative, anti-aging, anti-inflammatory, anti-cancer, anti-fatigue and anti-depressant activities. [13][14][15][16][17][18][19] Increasing evidence suggests that SA may have neuroprotective effects in injured brain. SA can reduce the degree of cerebral edema and the brain infarct size of rats with global cerebral ischemia, relieve the metabolism abnormity of free radicals and improve the function of cognition as well as behavioral and histological outcomes.…”
mentioning
confidence: 99%